Risk Factors for Caesarean Delivery Following Labour Induction - Iqbal, Iram; Ain, Noor-Ul-; Mazhar, Sobia (Biological and Clinical Sciences Research Journal, 2025)
Induction of labor (IOL) is a common obstetric intervention, yet it is frequently associated with varying success rates, particularly in low-resource settings. In Pakistan, identifying predictors of failed IOL remains critical to improving maternal and fetal outcomes. Objective: To determine the frequency and risk factors associated with failed induction of labor among pregnant women in a tertiary care hospital in Pakistan. Methods: This case-control study was conducted at the Department of Obstetrics and Gynaecology, Ibn-e-Siena Hospital, Lahore, from May 2024 to November 2024. A total of 136 pregnant women were enrolled, with 68 experiencing failed induction (cases) and 68 successful induction (controls). Data were collected through structured proformas, including demographic, obstetric, and clinical variables. Statistical analysis was conducted using SPSS version 25, with odds ratios and p-values calculated to determine associations. Results: The mean maternal age was 27.8 ± 4.6 years. Primigravidity (p=0.004), BMI ≥ 30 (p<0.001), post-term gestation (p=0.041), Bishop score <6 (p=0.001), intact membranes (p=0.045), and fetal macrosomia (p=0.014) were significantly associated with failed IOL. Closed cervix on admission also had a strong association with failure (p=0.007). Odds ratios showed that primigravidity and low Bishop scores doubled the likelihood of failed induction. Conclusion: Failed induction is strongly associated with modifiable and non-modifiable risk factors such as maternal BMI, parity, Bishop score, and gestational age. Tailored induction strategies and improved clinical decision-making protocols are needed to enhance maternal care outcomes in Pakistan.